The Savage Self: "Indians" and the Emergence of the Modern British Subject - Richardson, Robbie (My University, 2010)
This dissertation explores literary representations of North American Indigenous people in eighteenth-century British texts. Throughout the century, "Indians" appeared frequently in British print culture, in newspapers, periodicals, and travel narratives, but the primary focus in this work is on imaginative writing such as novels, plays, poetry, and essays. Many of these texts are surprisingly overlooked, and scholarship regularly diminishes the significance of Indians in literature during the period. I argue that these texts explore modernity through Indigenous subjectivity, and ultimately contribute to the shaping of modem British identity.
While the figure of the Indian is often thought of as a primitive "noble savage," Indians were also used to negotiate modem discourses which Britons were beginning to encounter throughout the eighteenth century. The important developments in British culture during the time, such as the forming of a unified British identity, the rise of capitalism and consumerism, and empire, impacted the lives and identities of Britons, and the Indian was used as a kind of "other self' to negotiate their effects. This dynamic began with texts surrounding the 1710 visit by four Iroquois "Indian kings" to London a few years following the Acts of Union, and increased mid-century as conflict in the colonies escalated. First Nations people began to play an important strategic role and were more frequently encountered by British soldiers and travellers, which led to a rise in textual representation in the metropolis. Both as critics of European culture and discursive sites upon which to project emerging cultural forces, Indians functioned as imagined modem subjects; by the end of the century, the figure of the Indian became appropriated by the Romantics and other writers, and the hybrid Briton who internalized Indigenous fortitude and cultural tenacity became the corrective to the decadence and corruption of European culture.
Keywords: British Subject; Indigenous; eighteenth-century; "Indians"